Hexanoic acid: a new potential substitute for copper-based agrochemicals against citrus canker - Caccalano, M. N. [UNESP]; Dilarri, G. [UNESP]; Zamuner, C. F.C. [UNESP]; Domingues, D. S. [UNESP]; Ferreira, H. [UNESP] (Oxford University Press (OUP), 2021)
Aims: The aim of the study is to evaluate hexanoic acid (HA) as an alternative to manage citrus canker. Methods and Results: The minimal growth inhibitory concentration of HA against Xanthomonas citri subsp. citri was determined at 2·15 mmol l−1 using a respiratory activity assay. Growth curves at different pH values showed that growth inhibition was not due to media acidification induced by HA. The germination rate and root elongation of Lactuca sativa seeds exposed to different concentrations of HA (varying from 0·86 to 5·16 mmol l−1) were assessed to screen for phytotoxicity. The acid exhibited low phytotoxicity for L. sativa at 1·29 and 2·58 mmol l−1. To evaluate the ability of HA to protect citrus against X. citri infection, leaves of Citrus sinensis were sprayed with the acid and subsequently challenged with X. citri. HA at 3·44 mmol l−1 was able to protect citrus against infection, showing a reduction of three orders of magnitude in the number of citrus canker lesions per cm2 when compared to the untreated negative control. Conclusion: HA is a potential alternative to copper for citrus canker management. Significance and Impact of the Study: HA inhibits X. citri growth, exhibits low phytotoxicity and is an alternative to copper for the protection of citrus plants against bacterial infection.
Keywords: cell division; disease management; membrane permeabilization; organic acid; phytotoxicity; Xanthomonas citri